Development of Student Creativity Based on Bilateral Cooperation Using the IPO Modification Method - Avicena, Azra Jinggan; Zahidi, M. Syaprin (Didaktika Religia, 2022)
This research seeks to uncover the formulation of the development of student creativity carried out by the Malang City Government in collaboration with MAN 2 Malang City, SMAN 1 Malang City, and SMAN 3 Malang City. The development of creativity enhances bilateral cooperation as a final result. This research is qualitative because the main data was taken through in-depth interviews with Malang City Public Relations as primary data. After conducting research, important things were found. First, in developing the creativity of students using the IPO method, it can be detailed as follows: 1) input, recruitment of students assisted by the Malang City Government including a delegation system from three schools; superior student system, tracing the achievements of students in Malang City, and; internalization of the mission as a formulation of concepts and segmentation. 2) process, including preparation (program, segmentation, targets, and time), implementation (organizing), and evaluation including follow-up plans and agreements with external parties including international. 3) output, including productivity (creative, cultural, and musical economy), innovation, and cooperation with European states. Second, the development of creativity results in bilateral cooperation with the country of Andorra in the field of the local economy and cultural performances. The concept of developing creativity is based on outcomes as evidenced by bilateral cooperation.